Coffee Processing Business Feasibility In BUMDes Eka Giri Karya Utama Wanagiri Village, Buleleng Regency Bali Province - Gunawitra, Putu Yuniary; Ustriyana, I Nyoman Gede; Budiasa, I Wayan (JURNAL MANAJEMEN AGRIBISNIS; Vol 12 No 1 (2024): Jurnal Manajemen AgribisnisDO - 10.24843/JMA.2024.v12.i01.p01, 2024)
The potential for good coffee plantation yields needs to be developed and utilized to improve the village economy, which is the basis for establishing BUMDes Eka Giri Karya Utama. The development of this business unit is aimed at supporting an integrated coffee processing industry and being able to produce more efficiently and be able to produce products according to dynamic market demands. The research objectives were to describe governance, to analyze financial feasibility, and to analyze the level of sensitivity of the coffee processing unit in BUMDes Eka Giri Karya Utama. This research was made using descriptive analysis and business feasibility analysis with the investment criteria used being NPV (Net Present Value (NPV), IRR (Internal Rate of Return), Net Benefit-Cost Ratio (Net B/C), Payback Period, and sensitivity analysis. The type of data used is primary data collected by in-depth interviews, field observations, and literature study. There are two variables in this study, namely the benefits and costs variables. The results of the study show that the Village Owned Enterprises in their establishment are managed with the spirit of wanting to improve the village economy, making the village an independent village with all the potential that exists in the village. BUMDes management is carried out in a professional, transparent, participatory, and sustainable manner. sources of funds for this business unit come from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration, and the local village government. Based on the results of the financial analysis, the NPV value was IDR 679,311,964.218, IRR was 31,60%, Net B/C was 2,85 and PP was 4 years 7 months 2 days. Furthermore, the results of the sensitivity analysis with an increase in operational costs by 25.18% obtained an NPV of IDR 434,079,320.45, an IRR of 23.17%, and a net B/C of 2.12. Then for the assumption of a 14.28% decrease in revenue, an NPV of IDR 388,934,679.50, an IRR of 22.02%, and a Net B/C of 2.02 are obtained. This coffee processing business unit is feasible. After all, it can provide benefits for the manager because it meets the investment criteria. Based on the sensitivity analysis, the assumption of a decrease in revenue is more sensitive than an increase in operational costs. In the future, for business development, managers need to innovate so that products become more attractive and have competitiveness as well as invest in human resources and marketing.